2019
DOI: 10.1186/s40001-019-0369-6
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of the kinematics of the rescuer in continuous chest compression during a 10-min simulation of cardiopulmonary resuscitation

Abstract: BackgroundIn pursuit of improvement in cardiopulmonary resuscitation (CPR), new technologies for the measurement and assessment of CPR quality are implemented. In our study, we assessed the kinematics of the rescuer during continuous chest compression (CCC–CPR). The proper performance of the procedure is a survival predictor for patients with cardiac arrest (CA). The purpose of the study was a prospective assessment of the kinematics of the rescuer’s body with consideration given to the depth and rate of chest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 32 publications
0
19
0
1
Order By: Relevance
“…In clinical settings, rescuers usually have to perform CPR in a kneeling or standing posture with their hands on the patient's sternum while keeping the upper limbs upright 19 , 20 , which is a very physically exhausting posture and movement. It can be found that a progressive reduction in the percentage of correct chest compressions after 1 minute of chest compressions 15 , 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%
“…In clinical settings, rescuers usually have to perform CPR in a kneeling or standing posture with their hands on the patient's sternum while keeping the upper limbs upright 19 , 20 , which is a very physically exhausting posture and movement. It can be found that a progressive reduction in the percentage of correct chest compressions after 1 minute of chest compressions 15 , 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Outra questão que teve aumento do conhecimento após a intervenção educativa foi relacionada ao posicionamento correto próximo a vítima, que influencia na qualidade e eficácia das compressões, pois a profundidade é determinada pelo peso da massa corporal do socorrista, ao posicionar com os braços perpendiculares ao tórax 23 .…”
Section: Discussionunclassified
“…This is related to the helper is possible not to keep his arms straight so that it will form movement in the elbow area. Bucki et al (2019) explain that movement in the elbow area does not affect the quality of the maneuver during compression. This research shows that the movement of a small elbow can reduce fatigue during chest compression procedures.…”
Section: Chest Recoilmentioning
confidence: 97%
“…The kneeling position becomes the position that has the smallest elbow movement compared to the standing position on the footstool and standing position on the floor. According to Bucki, Waniczek, Michnik, et al (2019), elbow movements are common when compressing the chest. This is related to the helper is possible not to keep his arms straight so that it will form movement in the elbow area.…”
Section: Chest Recoilmentioning
confidence: 99%